Comparative study of 16 clear-sky radiative transfer models to estimate direct normal irradiance (DNI) in Botucatu, Brazil - dos Santos, Cıćero Manoel; Escobedo, Joaõ Francisco [UNESP]; de Souza, Amaury; Ihaddadene, Razika; Gomes, Eduardo Nardini [UNESP]; da Silva, Maurıćio Bruno Prado [UNESP] (ASME International, 2021)
The interest of the direct normal irradiation (DNI) estimation is important in the evaluation of the solar potential and, consequently, for data correction and expansion of the historical series. In this study, a review of the performance of 16 models of radiative transfer was performed. These models are used to estimate DNI on a clear day in Botucatu/SP region located in Brazil. The revised models are categorized into two classes: simple models (11 models: ASH, MAJ, ALLEN, GH, P1, HLJ, FU, KU, H1, IP, and INC) and complex models (five models: BIRD, IQ, MRM5, P2, and YANG). The evaluation methodology used here is consistent with the literature. The input parameters were estimated and a statistical analysis using relative-mean-bias-error (rMBE), root-mean-square-error (rRMSE), and mean absolute percentage error (MAPE) indicators were performed to validate those models. The results indicate that the complex models (that require more atmospheric inputs) generally performed better than simpler models. Despite the consistent limitations in the use of estimated parameters, the performance of the models can be considered satisfactory. The best performances are highlighted for models MRM5 and YANG. Simple models ASH and IP performed similar to complex models. These results were confirmed using frequency distribution and the cumulative frequency analysis. These results are important for engineers of solar systems to use the best model and select the most suitable locations for installing a small or large solar plant.
Keywords: Atmospheric pollution; Cumulative distribution; Direct irradiance incidence; Frequency distribution; Parametric models; Statistical analysis